Integrated multi-omics analysis reveals the mechanisms of naringin in ameliorating high-fat diet-induced metabolic dysfunction-associated steatotic liver disease - Sun, Wenping; Xue, Na; Zhang, Qiang (Frontiers in Nutrition, 2025)
IntroductionNaringin (Nar), the predominant flavonoid in citrus fruits, shows therapeutic potential against metabolic dysfunction-associated steatotic liver disease (MASLD). However, its underlying mechanisms remain largely elusive.MethodsIn this study, we investigated the efficacy and underlying mechanisms of Nar in a mouse model of high-fat diet (HFD)-induced MASLD using integrated analyses of network pharmacology, molecular docking, hepatic lipidomics, and gut microbiota.ResultsTreatment with Nar markedly ameliorated MASLD phenotypes, as evidenced by reduced body and liver weights, lower hepatic triglycerides (TGs), and improved serum alanine aminotransferase (ALT) and aspartate aminotransferase (AST) levels. Network pharmacology analysis revealed that Nar targets associated with MASLD are primarily enriched in proteins such as SRC, AKT1, STAT3, FOS, ESR1, and NFKB1, which exert their effects through the PI3K-AKT signaling pathway. Molecular docking simulations further elucidated the interaction mechanisms. Lipidomic analysis revealed that Nar restored hepatic lipid homeostasis, significantly decreasing levels of TGs and diglycerides (DGs), with 20 differentially abundant lipid species identified as potential biomarkers. Additionally, Nar profoundly altered the gut microbial community, promoting the enrichment of beneficial genera including Oscillibacter, Allisonella, and Flavonifractor.DiscussionOur findings indicate that Nar prevents MASLD by harmonizing hepatic lipid metabolism and modulating the gut microbiome, providing a multifaceted mechanistic insight into its therapeutic potential.